Yearbook of the European Convention on Human Rights/Annuaire de la convention europeenne des droits de l'homme, Volume 49 A (Human Rights and Humanitarian Law - Book Archive 2000-2005., 2007)
For victims of human rights violations, human rights defenders are like a beacon of hope shining through the darkness of oppression. Through their work for the protection and realisation of human rights, injustices by authorities are unmasked, public awareness is raised and democratic control is exercised. Their devotion to fighting human rights violations, often at the risk of their own lives, cannot be praised too highly. The colloquy "Protecting and supporting human rights defenders in Europe", held in Strasbourg under the auspices of the Council of Europe, proved an ideal opportunity for frank and constructive exchanges between representatives of civil society and governments from the 46 member states of the Council of Europe on the obstacles encountered by human rights defenders in their work and the responses by the Council of Europe and other international actors to their concerns. This volume contains all the contributions to the plenary session as well as the reports from the three workshops.